Polska transformacja 1989-2009: aktorzy i przestrzenie = Polish transformation in the years 1989-2009: actors and spaces - Szczepański, Marek S.; Ślęzak-Tazbir, Weronika (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article, the work has the character of a sociological essay, is aimed at initial and fragmentary assessment of two decades of Polish transformation. Highlighted are social and spatial issues, although some references to economic, political or even ecological changes turned out to be unavoidable.
Keywords: transformacja ustrojowa; Polska; od 1989 r.